2018
DOI: 10.1155/2018/9140896
|View full text |Cite
|
Sign up to set email alerts
|

Antifatigue Potential Activity of Sarcodon imbricatus in Acute Excise‐Treated and Chronic Fatigue Syndrome in Mice via Regulation of Nrf2‐Mediated Oxidative Stress

Abstract: Sarcodon imbricatus (SI), a precious edible fungus, contains 35.22% of total sugar, 18.33% of total protein, 24 types of fatty acid, 16 types of amino acid, and 8 types of minerals. Encouragingly, it is rich in potential antioxidants such as total polyphenols (0.41%), total sterols (3.16%), and vitamins (0.44%). In the present study, the antifatigue properties of SI and its potential mechanisms of action were explored by the experiments on acute excise-treated mice and chronic fatigue syndrome (CFS) mice. SI (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 61 publications
3
42
0
Order By: Relevance
“…Lactic acid is formed and accumulated in muscle under the condition of high energy demand and insu cient oxygen supply [27]. The accumulation of lactic acid is very common in both CFS patients and animals [28,29]. It was previously reported that cistanche and ginkgo extracts could reduce the blood lactic acid level in mice and rats [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid is formed and accumulated in muscle under the condition of high energy demand and insu cient oxygen supply [27]. The accumulation of lactic acid is very common in both CFS patients and animals [28,29]. It was previously reported that cistanche and ginkgo extracts could reduce the blood lactic acid level in mice and rats [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides isolated from S. imbricatus have demonstrated to possess antibacterial [223], anti-myelosuppressive [224], and immunomodulatory activities [225,226]. Fruiting bodies and/or mycelial cultures have been reported to possess antioxidant [203,221], antimicrobial [132], and antifatigue activities [227]. Figure 17), nicotinic acid, 4-allylcatechol, uracil, ethyl β-Dglucopyranoside, propanetriol, uridine, adenosine and D-allitol were isolated from the fruiting bodies [220].…”
Section: Sarcodon Imbricatus (L) P Karstmentioning
confidence: 99%
“…Polysaccharide [208,211], Extract [203,213,214] ---Sarcodon imbricatus (L.) P. Karst (Bankeraceae) Extract [203,219,221] Extract [22,132,217,218], Polysaccharide [223] -Extract (immunomodulatory [216] and antifatigue activities [227]). Polysaccharide (immunoenhancement [225,226] and anti-myelosuppressive activities [224]).…”
Section: Thelephora Ganbajun M Zangmentioning
confidence: 99%
“…The “exhaustion theory,” “radical theory,” “protective inhibition theory,” “clogging theory,” and “hemoglobin theory” are five main theories to explain the mechanisms of fatigue (Lamou et al., 2016). Based on the “radical theory,” overproduction of reactive oxygen species (ROS) can induce oxidant to disturb antioxidant defense system and homeostatic environment through oxidative stress (Wang et al., 2018). Moreover, lipid peroxidation caused by ROS leads to fatigue by attacking large molecules and muscles, especially in the diaphragm (Hasegawa, Suzuki, Matsumoto, & Okubo, 1997).…”
Section: Introductionmentioning
confidence: 99%